Researchers' attitudes towards the use of social networking sites. Issue 1 (12th October 2017) - Greifeneder, Elke; Pontis, Sheila; Blandford, Ann; Attalla, Hesham; Neal, David; Schlebbe, Kirsten
Abstract : Purpose: The purpose of this paper is to better understand why many researchers do not have a profile on social networking sites (SNS), and whether this is the result of conscious decisions. Design/methodology/approach: Thematic analysis was conducted on a large qualitative data set from researchers across three levels of seniority, four countries and four disciplines to explore their attitudes toward and experiences with SNS. Findings: The study found much greater scepticism toward adopting SNS than previously reported. Reasons behind researchers' scepticism range from SNS being unimportant for their work to not belonging to their culture or habits. Some even felt that a profile presented people negatively and might harm their career. These concerns were mostly expressed by junior and midlevel researchers, showing that the largest opponents to SNS may unexpectedly be younger researchers. Research limitations/implications: A limitation of this study was that the authors did not conduct the interviews, and therefore reframing or adding questions to specifically unpack comments related to attitudes, feelings or the use of SNS in academia was not possible. Originality/value: By studying implicit attitudes and experiences, this study shows that instead of being ignorant of SNS profiles, some researchers actively opt for a non-use of profiles on SNS.